Validation of Problem-Based Learning Teaching Modules on Momentum and Impulse to Improve Students' Critical Thinking Skills - Sekarani, Tresnane Suandti; Akhsan, Hamdi; Kistiono, Kistiono (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to validate a Problem-Based Learning (PBL) teaching module on Momentum and Impulse material to improve the critical thinking skills of Grade XI students. The validation ensures the module's feasibility before implementation in the classroom. Methodology: This research and development (R&D) study used the Four-D Model (Define, Design, Develop, Disseminate), limited to the development stage. Validation involved four experts who assessed the module using a validation questionnaire. Data were analyzed quantitatively based on content, construct, language, presentation, and assessment criteria. Main Findings: The module received an average validity score of 89%, categorized as